The Effectiveness of the Guided Reading Method on Students’ Ability to Evaluate Negotiation Texts in Grade X/Phase E at Senior High School - Sutanti Ramli; Asna Ntelu; Muslimin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the effectiveness of the Guided Reading method on students’ ability to evaluate negotiation texts. This research employed a pre-experimental design with a one-group pre-test and post-test approach. The participants of this study were 30 tenth-grade students of Senior High School. The data were collected through a reading test and analyzed using a paired sample t-test. The results showed a significant improvement in students’ ability, as indicated by the increase in the mean score from 39.00 in the pre-test to 80.17 in the post-test. The t-test analysis revealed a statistically significant difference (p = 0.000 < 0.05), indicating that the Guided Reading method had a significant effect on students’ evaluative reading ability.This improvement occurred because the Guided Reading method promotes guided analysis and critical engagement with text structure and content, enabling students to better understand, interpret, and evaluate negotiation texts. In conclusion, the Guided Reading method is effective in improving students’ ability to evaluate negotiation texts and can be recommended as an alternative strategy in teaching reading comprehension, particularly in developing students’ critical thinking skills.